2020
DOI: 10.1070/qel17396
|View full text |Cite
|
Sign up to set email alerts
|

Development and study of high-power quantum-cascade lasers emitting at 4.5 – 4.6 μm

Abstract: Quantum-cascade room-temperature 4.5 – 4.6 μm lasers with different numbers of quantum cascades are developed and studied. It is shown that losses at the metallised sidewalls of the ridge waveguide considerably increase the threshold current density. It is demonstrated that the current density needed to overcome the internal and outcoupling losses in lasers with 30 quantum cascades is an order of magnitude lower than in lasers with 15 quantum cascades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The maximum obtained power of 13 W at a wavelength of 8 μm is a record for this spectral range. The results were reported in a series of works in the Quantum Electronics Journal [ 62 64 ].…”
Section: Research Direction 135 Optics and Laser Physicsmentioning
confidence: 99%
“…The maximum obtained power of 13 W at a wavelength of 8 μm is a record for this spectral range. The results were reported in a series of works in the Quantum Electronics Journal [ 62 64 ].…”
Section: Research Direction 135 Optics and Laser Physicsmentioning
confidence: 99%
“…Thus, in the course of research, results were obtained on the creation and study of the QCL characteristics of the spectral range 4. tures fully grown by the MPE [10] method. Considering the fact that strip QCLs made from heterostructures fully grown by the MPE method demonstrate high optical output power (at the level of 10,W) [13,14], it can be concluded that the combined approach in epitaxy of heterostructures is promising to implement powerful QCLs of the spectral range 4.6 µm. At the same time, increasing the number of cascades to 45 can further increase the output optical power in comparison with the previously presented results [14], which is the subject of further research.…”
mentioning
confidence: 99%